Research on the Soot Generation of Diesel Surrogate Mechanisms of Different Carbon Chain Length - Xingyu Liang; Zhijie Zhu; Xinyi Cao; Kun Wang; Yuesen Wang (Energies, 2022)
This paper studies the generation process and emission characteristics of soot from Marine diesel engine. On the basis of Particulate size mimic (PSM) detailed soot model, the parameters related to soot generation obtained from the reaction mechanism calculation of 3 surrogate of different carbon chain length: n-heptane, n-tetradecane and n-tetradecane-toluene were compared and analyzed including precursor of soot, quality and density of soot, particle size distribution of empirical soot model. The results show that the soot nucleation stage of n-tetradecane-toluene mechanism was slightly more consistent than that of n-tetradecane mechanism with the experimental results, far more consistent than that of n-heptane mechanism. The intensity of surface growth and aggregation stage is greater, which is reflected in the soot precursor: acetylene and A4, and leads to that the soot produced by the mechanism of n-tetradecane and n-tetradecane-toluene is small in quality but large in quantity. The particle size distribution calculated by n-tetradecane and n-tetradecane-toluene mechanism is closer to the experimental data than that calculated by n-heptane mechanism. Then combustion process of n-tetradecane and n-tetradecane-toluene mechanism is more suitable for marine engine, which is reflected in the higher temperature and the smaller equivalent ratio in the cylinder.